2009
DOI: 10.23986/afsci.5964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perch on feed consumption and behaviour of caged laying hens

Abstract: This experiment studied the effects of perches in furnished cages on behaviour and feed consumption of laying hens. The study used 352 Lohmann Selected Leghorn (LSL) hens. The hens were housed at 16 weeks of age in furnished cages in groups of 8 birds. The experiment lasted for 205 days. The treatments were: perches present from 16 weeks of age (P16), perches present from 19 weeks of age (P19), and no perches present (NP). Feed consumption and egg production were measured over the pre-laying period and six 4-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Perch use in this study (around 5% of hens observed perching at the time of visit, Table 1 ) was lower than a previously reported daytime perch use of 10% [ 20 ] or even higher values (> 25%) reported for example by Valkonen et al [ 21 ] and Barnett et al [ 22 ]. This could be related to less accurate recording (a single time point per day) vs the continuous monitoring that was used in some of the other studies and also due to the specific pen design.…”
Section: Resultscontrasting
confidence: 75%
“…Perch use in this study (around 5% of hens observed perching at the time of visit, Table 1 ) was lower than a previously reported daytime perch use of 10% [ 20 ] or even higher values (> 25%) reported for example by Valkonen et al [ 21 ] and Barnett et al [ 22 ]. This could be related to less accurate recording (a single time point per day) vs the continuous monitoring that was used in some of the other studies and also due to the specific pen design.…”
Section: Resultscontrasting
confidence: 75%
“…Perch utilization during the light period observed in this study (10% of the light period at 9 WPE) was much lower than that reported in earlier studies (ranging between 25-50%). Tauson (1984) reported hens perching 25-50% of the daytime, while others reported hens spending about 25% of the daytime on perches (Appleby et al, 1992;Valkonen et al, 2009). Yet, some studies reported that hens spent about 32-38% of the daytime on perches (Newberry et al, 2001;Barnett et al, 2009).…”
Section: Diurnal and Temporal Perching Behavior Of Laying Hensmentioning
confidence: 99%